Türk Hukukunda Kurgusal Karakterlerin Korunması - (:unkn) unknown (My University, 2016)
Kurgusal karakterler, içerisinde yer aldıkları fikir ve sanat eserinin önemli bir parçasını oluştururlar. Sahip oldukları bu önemli konum onların içerisinde yer aldıkları eserden bağımsız olarak da korunmalarını gerektirmektedir. Bu çalışmada 5846 Sayılı Fikir ve Sanat Eserleri Kanunu kapsamında kurgusal karakterlere sağlanan koruma ele alınacaktır. Türk hukukunda, eserlerde aranan unsurları barındırmaları şartıyla bunların bağımsız bir eser olarak korunması mümkündür. Ancak grafik karakterler ve diğer karakterlerin korunması açısından farklı hükümlere başvurmak gerekmektedir. Söz konusu unsurları barındırmayan kurgusal karakterler ise haksız rekabet hükümleri çerçevesinde korunabilir.

Fictional characters plays a crucial role within the scope of the intellectual and artistic work which it forms the part of. This particular situation necessitates that its copyright shall be protected independently of the work in which it is included. The purpose of this study is to examine the protection provided for the fictional characters under the Law No. 5846. Under Turkish Law, a fictional character may be protected as an independent work, provided that it includes the elements required for a production to be considered as a work. However, with respect to the protection of the graphic characters or other characters, different provisions shall be referred. Characters not containing these elements may be protected under the provisions of the unfair competition.
Protection of Fictional Characters in Turkish Law
Keywords: Hukuk